Adoption Lag Minimization for Increasing Rice Yield - Karmakar, B; Rahman, MM; Sarkar, MAR; Mamun, MAA; Rahman, MC; Nessa, B; Salam, MU; Kabir, MS (Bangladesh Rice Journal, 2021)
Sustainable adoption of promising technology leads to increase yield and productivity of rice significantly. Yield gap reduction through minimization of adoption cycle of rice technologies is essential to increase food security of Bangladesh. Adoption of promising rice variety required 16±3 years to reach its adoption peak at farm level following the existing dissemination protocol. The specific objective is to find out the ways and means to curtail adoption lag of variety, management practices and rice based technologies for sustainable food security of Bangladesh. The study is accomplished accordingly by reviewing previous works completed on technology adoption; calculation and estimation of future seed demand and supply. Our findings reveal that the average yield gap between actual farm yield and potential farm yield is 20.7%. Seed retention and motivated farmers estimated from the frontline demonstrations of BRRI were 18 and 20%, respectively. Sufficient amounts (128 kg/variety) of breeder seed need to be produced by the concerned research organizations concurrently the variety release process. The seed will be used to execute action plan by setting up 64 adaptive trials (AT) in 64 districts to select location specific suitable variety(s) for rapid dissemination. In the 2nd and 3rd years, 256 kg quality seeds per variety will be required to conduct 128 AT/SPDP in 64 districts. The seed of farmers’ chosen variety(s) will be collected, stored, and marketed by the local seed producer or farmers group; and they will provide this information to the extension organization and BRRI. At least 10 to 20% seed selling information will be checked by the concerned scientist of BRRI every year and total seed selling data will be calibrated based on the checked data. Similarly, the next two years’ trial data will be collected from conducted trials and associated seed producer/dealer/farmers’ club/groups. Then, the concerned research institute will be able to provide a projection of diffusion rate and demand of newly released variety(s) compiling three years data. Based on the authentic reports, the concerned organizations will conduct block, frontline and follow-up demonstrations in collaboration with all the stakeholders. Action plan of research and extension; large scale frontline demonstration of the selected variety(s) with more stakeholders followed by field day, training, and workshop would be the key drivers for effective and sustainable dissemination of technology lead to reduce adoption lag effectively. Combined initiatives and integrated approaches need to be taken nationally to execute the adoption lag minimization plans and model for rapid dissemination of promising technology to doubling the rice productivity. Therefore, popularization and adoption of new technology would be possible within five to seven years instead of 16±3 years. Bangladesh Rice J. 25 (1) : 75-88, 2021